Efektivitas Prinsip Komunikasi Islam Guru dalam Pembinaan Karakter Komunikasi Siswa Kelas X MAN Rantauprapat - Junita Junita; Zainuddin Zainuddin; Ibnu Hajar; Rahma Muti’ah; Marlina Siregar (JUPIIS: JURNAL PENDIDIKAN ILMU-ILMU SOSIAL, 2021)
This study aims to obtain a concrete picture of the effectiveness of the application of the principles of teacher Islamic communication in fostering the character of tenth grade students of Madrasah Aliyah Negeri Rantauprapat. The communication process in education is not only understood as a one-way knowledge transfer process, however, there must be a serious effort on the part of the educator / teacher, as a communicator, to be able to provide good role models. Qualitative research methods try to understand a phenomenon as the understanding of the respondents studied, with an emphasis on the subjective aspects of one's behavior. Qualitative research provides an opportunity for researchers to understand the way respondents describe the world around them based on the way they think. The researcher tries to enter the conceptual world of the subject under study to capture what and how things happen. Data collection techniques used in this study were interviews in this study researchers used a semi-structured interview (semitructure interview), namely: interviews in the category of in-depth interviews. Data about the application of teacher Islamic communication and the communication character of tenth grade students, data analysis used in this study during the field using the Miles and Huberman Model, namely the activities in qualitative data analysis are carried out interactively and continue continuously until completion, so that the data is already saturated.